Trauma: An Ideology in Search of Evidence and its Implications for the Social in Social Welfare. Issue 4 (November 2021) - Smith, Mark; Monteux, Sebastian; Cameron, Claire
Abstract : A recent special issue of this journal focussed on the emergence of the Adverse Childhood Experiences (ACEs) movement as a key driver of Scottish social policy. In this article, we extend the critiques advanced therein by locating ACEs within a wider cultural turn towards psychological trauma which, over the past decade, has become reified as a master theory across social welfare. Yet, the concept is insubstantial and ill-defined, and the claims made for policy based upon it are at best disputable. Its prominence is less evidence-based than it is testimony to how a particular (cultural and professional) ideology, regardless of its intellectual merit, can be insinuated into policy discourse. ACEs, we suggest, is utilised to provide the trauma paradigm with some ostensibly quantifiable substance. We illustrate our argument through reference to the Scottish Government's National Trauma Training Programme (2020). We go on to consider some of the implications of such ideological capture for the direction of Scottish social welfare policy and practice. The prominence given to trauma perspectives has potentially iatrogenic consequences for those identified or self-identifying as traumatised. At a wider level, it reflects a professional and epistemic privileging of a narrow, ostensibly therapeutic, worldview which, in turn, acts to marginalise 'the social' that characterised erstwhile Scottish approaches to welfare.